PERENCANAAN SABO DAM KALI PUTIH (KM 16,7) KABUPATEN MAGELANG JAWA TENGAH - Nanda Anjariwibowo; Dwi Indra Setyawan; Salamun Salamun; Hary Budieny (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Mount Merapi (2980) meters above sea level), one of the most active volcanoes in the world, located in Central Java Province. Mt. Merapi last erupted in 2012, producing a large number of volcanic materials which has highly destructive force. This flow happened on almost all of the rivers in Mt. Merapi hillside, such as Kali Putih for example. Kali Putih has a big potential of damage because of its location, near rural areas. Reffering to the above mentioned, the preventive effort of disasterous effect need to be done to decrease the damages by using Sabo Dam. The data we need to design it are hydrological data such as annual daily rainfalls data and Kali Putih catchment area map, soil investigation data, a topographic map and geometric river map. Those data will be processed and used as the basis for designing the Main Sabo Dam, Sub Sabo Dam, Apron and etc. The results of Sabo Dam design are: total height of Main Dam is 8,55 meters, total height of Sub Sabo Dam is 2,79 meters, length of Apron is 6,1 meters, sediment storage capacity is 8.100 m3, the total cost is Rp.1.470.615.000,00 (including VAT) and the construction phase is 14 weeks. The construction of Sabo Dam will be more optimal if it is accompanied by a good maintenance system done by the related agencies, so that the percentage of the damaged covering areas will decrease significantly.